Spatial Distribution of PCB Dechlorinating Bacteria and Activities in Contaminated Soil - Birthe V. Kjellerup; Piuly Paul; Upal Ghosh; Harold D. May; Kevin R. Sowers (Applied and Environmental Soil Science)
Soil samples contaminated with Aroclor 1260 were analyzed for microbial PCB dechlorination potential, which is the rate-limiting step for complete PCB degradation. The average chlorines per biphenyl varied throughout the site suggesting that different rates of in situ dechlorination had occurred over time. Analysis of PCB transforming (aerobic and anaerobic) microbial communities and dechlorinating potential revealed spatial heterogeneity of both putative PCB transforming phylotypes and dechlorination activity. Some soil samples inhibited PCB dechlorination in active sediment from Baltimore Harbor indicating that metal or organic cocontaminants might cause the observed heterogeneity of in situ dechlorination. Bioaugmentation of soil samples contaminated with PCBs ranging from 4.6 to 265 ppm with a pure culture of the PCB dechlorinating bacterium Dehalobium chlorocoercia DF-1 also yielded heterologous results with significant dechlorination of weathered PCBs observed in one location. The detection of indigenous PCB dehalorespiring activity combined with the detection of putative dechlorinating bacteria and biphenyl dioxygenase genes in the soil aggregates suggests that the potential exists for complete mineralization of PCBs in soils. However, in contrast to sediments, the heterologous distribution of microorganisms, PCBs, and inhibitory cocontaminants is a significant challenge for the development of in situ microbial treatment of PCB impacted soils.